PERANCANGAN APLIKASI KAMUS BAHASA TORAJA MENGGUNAKAN METODE RAPID APLICATION DEVELOPMENT - Seldi, Yestiani; Handoko, Koko (LPPM Universitas Putera Batam, 2023)
One of the efforts that can be made to prevent extinction and support the preservation of the Toraja language is to provide a Toraja language dictionary.However, the dictionary was only printed in small quantities so that it could not be accessed by the public at large and there was a decrease in interest in printed versions of dictionaries which were considered already out of date and being replaced by digital dictionaries that are more flexible and practical in their use. In this study using the Rapid Application Development (RAD) method, which is the RAD method, is a method that focuses on developing applications quickly through repeated development and feedback that matches the short target application development time but still adheres to the following stages: stages in making an application. The purpose of this research is to make a Toraja language dictionary application to support the preservation of the Toraja language, prevent the threat of extinction of the Toraja language and introduce Toraja language to the general public outside Tana Toraja. Developments in internet technology and mobile devices make it possible to create dictionaries in web or application form.